2015
DOI: 10.1016/j.childyouth.2015.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent drinking in Spain: Family relationship quality, rules, communication, and behaviors

Abstract: This study examined associations between adolescent alcohol use in Spain and family relationship quality, parental rules, sources of information about substances, and family behaviors. A sample of 565 students in Alicante, Spain completed measures of these constructs.After controlling for age and type of school, family relationship quality explained 3.7% of the variance in adolescents' alcohol use, family rules explained 7.0%, sources of information 2.8%, and parental behaviors 2.6%. A comprehensive model with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
(32 reference statements)
1
8
0
1
Order By: Relevance
“…Based on this finding, it appears that open communication with parents protects children from experiencing school adjustment problems, low self-esteem, depression and substance use. These findings are in keeping with previous studies that also established a relationship between quality of parent-child communication and substance use (Goldberg-Looney et al, 2015;Luk et al, 2010;Ryan et al, 2010;Tobler & Komro, 2010); self-esteem and good parent-child communication (Hartos & Power, 2000;Park & Koo, 2009;Riesch et al, 2006); depression and parent-child communication (Yu et al, 2006) and school adjustment and parent-child communication (Demaray & Malecki, 2002;Esteyez et al, 2005;Riesch et al, 2006). In line with the family system theory, the present study demonstrated that parents would continue to influence children's psychological adjustment through their continuous interactions and quality of communication.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Based on this finding, it appears that open communication with parents protects children from experiencing school adjustment problems, low self-esteem, depression and substance use. These findings are in keeping with previous studies that also established a relationship between quality of parent-child communication and substance use (Goldberg-Looney et al, 2015;Luk et al, 2010;Ryan et al, 2010;Tobler & Komro, 2010); self-esteem and good parent-child communication (Hartos & Power, 2000;Park & Koo, 2009;Riesch et al, 2006); depression and parent-child communication (Yu et al, 2006) and school adjustment and parent-child communication (Demaray & Malecki, 2002;Esteyez et al, 2005;Riesch et al, 2006). In line with the family system theory, the present study demonstrated that parents would continue to influence children's psychological adjustment through their continuous interactions and quality of communication.…”
Section: Discussionsupporting
confidence: 92%
“…For example, many studies have established that poor parent-adolescent communication is associated with increased risky sexual behaviour (Atienzo, Walker, Campero, Lamadrid-Figueroa, & Gutiérrez, 2009;Rogers, Ha, Stormshak, & Dishion, 2015). Research also indicates that parents who communicate with their children openly and who involved them in discussions have children who are less involved in tobacco and alcohol use (Goldberg-Looney et al, 2015;Luk, Farhat, Iannotti, & Simons-Morton, 2010;Ryan, Jorm, & Lubman, 2010;Tobler & Komro, 2010). These studies conclude that parents play an important role in their children healthy development as they communicate their opinions and disquiets about substance use and expectations for appropriate behaviour directly to them.…”
Section: Communication and Children's Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…In explaining the finding that loneliness due to relationship with family in athlete women is lower than of nonathlete women, it can be said that family relations quality indicators include warmth, supportive parental relationship, positive control, and sense of belonging (Goldberg-Looney et al, 2015). For this reason, if the need for feeling of belonging is not satisfactory, negative feelings such as loneliness are created (Sawir et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, factors contributing to the development of adolescent alcohol use have been explored in order to create effective, efficient intervention strategies, and researcher found that family, school, and peers were closely associated with adolescents’ alcohol use 13,14. The effect of schooling on students has long been of interest to educational researchers and policymakers 15.…”
Section: Introductionmentioning
confidence: 99%